2012
DOI: 10.1002/eat.20973
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐reported energy intake in weight‐restored patients with anorexia nervosa compared with obese and normal weight individuals

Abstract: Objective To compare self-reported and measured energy intake in weight-restored patients with anorexia nervosa (AN), weight-stable obese individuals (OB), and normal weight controls (NC). Method Forty participants (18 AN, 10 OB, and 12 NC) in a laboratory meal study simultaneously completed a prospective food record. Results AN patients significantly (p = .018) over-reported energy intake (16%, 50 kcal) and Bland-Altman (B-A) analysis indicated bias toward over-reporting at increasing levels of intake. OB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…The few studies that have used a covertly measured food intake as the reference have shown 271 mixed results -either no effect of BMI on the degree of misreporting (9,22), that obese 272 subjects are more accurate in reporting their food intake than are overweight or lean subjects 273 (23), or less accurate (8). Most of these studies have used diet recalls completed after the 274 covert food intake measurement rather than concurrent measures thereby introducing a 275 further source of uncertainty into the dietary intake method since the recall method relies on 276 the ability and motivation of subjects to remember what was eaten.…”
Section: Discussion 228mentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that have used a covertly measured food intake as the reference have shown 271 mixed results -either no effect of BMI on the degree of misreporting (9,22), that obese 272 subjects are more accurate in reporting their food intake than are overweight or lean subjects 273 (23), or less accurate (8). Most of these studies have used diet recalls completed after the 274 covert food intake measurement rather than concurrent measures thereby introducing a 275 further source of uncertainty into the dietary intake method since the recall method relies on 276 the ability and motivation of subjects to remember what was eaten.…”
Section: Discussion 228mentioning
confidence: 99%
“…More direct evidence is 62 harder to find, although weight stable obese subjects under-reported energy intake from a 63 buffet meal, whereas normal weight subjects accurately reported intakes (8). Perhaps 64 unsurprisingly weight restored patients with anorexia nervosa over-reported energy intake in 65 the same study (8). When a measure of true food intake is available for periods of a day or 66 two-weeks, group average reported energy intakes are lower than actual energy intakes, and 67 most individuals under-report their food intake, although a small number do over-report (7, 68 9).…”
Section: Introduction 45mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our study did not assess for other factors unrelated to restriction (e.g., negative affect) that may lead to binge eating. Furthermore, height, weight, dietary behaviors and binge eating episodes were assessed by self-report questionnaire which does not address the possibility of participants providing inaccurate data by over-or under-reporting, although some studies suggest that individuals with eating disorder symptoms may provide accurate self-reported height, weight (32) and food intake data (25)(26)(27).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Anorexia nervosa patients significantly over-reported energy, and probably protein intake [92], notwithstanding the unreported use of purging means such as vomiting and laxatives [93,94]. Nevertheless, protein depletion associated with low lean body mass has been clearly identified in anorexia nervosa patients [95].…”
Section: Anorexia Nervosamentioning
confidence: 99%